2019
DOI: 10.31788/rjc.2019.1215013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Intersection Absorption Spectrum for Simultaneous Determination of Betamethasone Valerate and Neomycin Sulfate in Cream

Abstract: Betamethasone valerate and neomycin sulfate are combinations of anti-infection in skin cream. The purpose of this study was to validate intersection absorption spectrum methods and simultaneous determination of betamethasone valerate and neomycin sulfate in the skin cream using 70% ethanol as solvent. The simultaneous determination of a sample was performed with the intersection point spectrophotometric methods when betamethasone valerate and neomycin sulfate absorption spectrum were overlapped and the interse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Based on Indonesian pharmacopeia, the analysis on neomycin sulfate is using microbial testing [5]. Another study shown that absorption ration and chemometric spectrophotometry methods was valid for determination betamethasone valerate and neomycin sulfate in cream [8], [9]. Thus, the present study aimed to make a formula containing vitamin E and make a comparison of determine levels of betamethasone valerate and neomycin sulfate in creams using High Performance Liquid Chromatography and Spectrophotometry Area Under Curve methods.…”
Section: Thementioning
confidence: 99%
“…Based on Indonesian pharmacopeia, the analysis on neomycin sulfate is using microbial testing [5]. Another study shown that absorption ration and chemometric spectrophotometry methods was valid for determination betamethasone valerate and neomycin sulfate in cream [8], [9]. Thus, the present study aimed to make a formula containing vitamin E and make a comparison of determine levels of betamethasone valerate and neomycin sulfate in creams using High Performance Liquid Chromatography and Spectrophotometry Area Under Curve methods.…”
Section: Thementioning
confidence: 99%
“…Besides that, this technique is successfully applied to all analytical methods in spectrophotometry [4]. Spectrophotometry ratio absorbance and area under the curve are two valid modified to quantify BET and NEO in cream [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3] Assays of Metformin and Glibenclamide in a single form was determined with maximum absorption at wavelengths of 236 nm for Metformin and 229 nm for Glibenclamide by the ultraviolet spectrophotometry method and an HPLC methods. [4][5] Various studies have been published for quantitative determination methods for simultaneous assays of drug mixtures have been developed by researchers using the HPLC method 6 , RP-HPLC 7 , matric methods 8 , intersection absorption spectrum method 9 , UV-visible spectrophotometry. [10][11] The combinations of Metformin and Glibenclamide preparations have adjacent absorption and interfere with each other simultaneously assay with the classic spectrophotometry method.…”
Section: Introductionmentioning
confidence: 99%